Sistem Penjadwalan Pelayanan Perbaikan Komputer Menggunakan Algoritma Round Robin - Umniy Salamah; Vincentius Krisna Aditya; Yuwan Jumaryadi; Vina Ayumi; Handrie Noprisson (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Computer devices do not always function properly. There are times when the device is damaged, and the user of the device will try to repair it by going to a service center or computer repair shop. Of course, in this case, the user will lose time and energy. Therefore, the design of a mobile web-based computer device repair service application is needed because this application can make it easier for device users to order computer device repair services online according to our needs and can be accessed anywhere without time and place restrictions. The research was conducted using a descriptive method that attempts to describe objects as they are in reality. The aim of this research is to determine the status of the device being serviced. This application was created using the Web programming language PHP, HTML, CSS using a MySQL database. The research carried out was able to develop an information system that helps in ordering computer equipment repairs.